The one minute manager meets the monkey - Blanchard, Kenneth H.; Oncken, William; Burrows, Hal, 1937- (New York : Morrow, 1989)
Teaches managers how to become effective supervisors of time, energy, and talent.
The problem -- First management position -- Meeting with boss -- Meeting with the One Minute Manager -- Fundamental management dilemma -- Diagnosis: self-inflicted problem -- Definition of a monkey -- Who owns the monkey? -- Vicious cycle -- The solution -- The One Minute Manager's awakening -- The depth of the problem -- Rescuing -- A feeling of optimism -- Returning the monkeys -- Having time for my people -- Onchen's rules of monkey management : Rule 1: Descriptions ; Rule 2: Owners ; Rule 3: Insurance policies ; Rule 4: Feeding and checkups -- A summary of Oncken's four rules of monkey management -- Delegation -- Coaching -- Balancing three kinds of organizational time : Boss-imposed time ; System-imposed time ; Self-imposed time -- Discretionary: the most vital time -- Starting with subordinate-imposed time -- Planting discretionary time -- Managing rather than doing -- The ultimate conversion.
Keywords: Time management; Executives -- Time management; Delegation of authority